2022
DOI: 10.1021/acs.est.2c05753
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicity and Teratogenicity of Fluorene-9-bisphenol on Chinese Medaka (Oryzias sinensis): A Study from Laboratory to Field

Abstract: Fluorene-9-bisphenol (BHPF), a bisphenol A (BPA) substitute, has been increasingly used as a material in syntheses of polymers that are widely used in road markings, artificial tracks, coating floors, building paints, etc., increasing the likelihood of BHPF contamination in the aquatic environment due to its release from the products. However, to date, it is unknown whether it may have actual impacts on fish in real environments. In this study, a 105-day exposure experiment of BHPF at various concentrations (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Intriguingly, our data revealed an upregulation of the Pou4F2 gene, a known marker for retinal ganglion cells, suggesting potential implications for visual development ( Badea and Nathans, 2004 ). This observation is consistent with recent findings in which eye malformation was reported in Chinese Medeka, a teleost fish, following exposure to BHPF at different concentrations for 105 days ( Fan et al, 2023 ). The upregulation of Pou4F2 and the associated eye malformation highlight the need for further studies to explore the impact of BHPF on visual development.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Intriguingly, our data revealed an upregulation of the Pou4F2 gene, a known marker for retinal ganglion cells, suggesting potential implications for visual development ( Badea and Nathans, 2004 ). This observation is consistent with recent findings in which eye malformation was reported in Chinese Medeka, a teleost fish, following exposure to BHPF at different concentrations for 105 days ( Fan et al, 2023 ). The upregulation of Pou4F2 and the associated eye malformation highlight the need for further studies to explore the impact of BHPF on visual development.…”
Section: Discussionsupporting
confidence: 93%
“…However, the potential toxicological impact of BHPF is still not fully understood. Moreover, BHPF has been found in household dust, further elevating concerns about widespread exposure ( Fan et al, 2023 ). Due to the growing public concern and regulatory pressure over BPA safety, some BPA alternatives have been introduced, such as BHPF.…”
Section: Introductionmentioning
confidence: 99%
“…Although this cannot be considered conclusive, it is interesting because fetus of pregnant participants with the highest levels of BHPF may develop VSD, suggesting that BHPF poses a potential threat to human fetal heart development. As humans and animals are exposed to environments polluted by BHPF [ 38 ], these findings should be made known to reduce environmental BHPF pollution and to promote further investigations on BHPF-mediated effects, including large-scale population studies. Furthermore, owing to the widespread application of BHPF-containing plastics, BHPF-releasing sources might already be inside human and animal bodies.…”
Section: Discussionmentioning
confidence: 99%
“…STING1) are also available, suggesting multiple potential therapeutic strategies targeting BHPF-induced adverse effects [ 43–45 ]. In addition to the frequent presence in serum of pregnant people, a recent report showed that BHPF is detectable in 60% of surface waters in Beijing, China [ 38 ], further highlighting the urgency for unveiling BHPF-mediated cardiovascular defects as well as potential therapeutic countermeasures. Our preclinical trial shows that sapropterin dihydrochloride can rescue heart failure in cardiomyocyte-specific Ythdf2 conditional knockout mice ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medaka has multiple advantages similar to the Japanese medaka, such as small body size, short generation time, genetic sexual determination, and well-annotated genomic information [ 38 ]. Furthermore, it is distributed in most parts of East Asia, and is convenient and suitable for both laboratory and field investigations [ 39 ]. The present study aims to examine the acute toxicity, developmental defects, and transcriptional alterations induced by BPF exposures in Chinese medaka embryos and provide information for understanding the health effects and ecological risk evaluation of BPF.…”
Section: Introductionmentioning
confidence: 99%